Plasmacytoid Myoepithelioma of the Hard Palate: Case Report - Christina Efthymia Souliou; Fotios Tzermpos; Prokopios Argyris; Konstantinos Tosios (University of Zagreb. School of Dental Medicine, 2017)
Background: Myoepitheliomas are uncommon salivary gland neoplasms consisting entirely or predominantly of cells with myoepithelial phenotype. They commonly involve the parotid gland and the minor salivary glands of the palate. Aim: A case of plasmacytoid myoepithelioma of the hard palate is described. Case description and results: A 55-year-old woman presented to her oral surgeon with a tumor on the hard palate. Microscopic examination showed a well-circumscribed but non-encapsulated tumor, consisting mostly of plasmacytoid cells in a loose fibrovascular stroma. Neoplastic myoepithelial cells showed immunoreactivity for S-100 protein, CK AE1/AE3 (Figure 5b), GFAP, calponin, and D138/Syndecan-1. Total excision of the tumor under local anesthesia was performed and no recurrence was noted 14 months after treatment. Conclusions: Since plasmacytoid myoepithelioma is uncommon, minor salivary glands, its immunohistochemical features, management and prognosis should be further investigated.